Placental site trophoblastic tumor with perimetrial invasion and cesarean scar perforation (A case report) - Gurung, Geeta; Amatya, Archana; Thakur, Nupur; Rana, Ashma (Nepal Journal of Obstetrics and Gynaecology, 2008)
Placental site trophoblastic tumor (PSTT) a rare variety of gestational trophobalstic neoplasia described in younger women, usually following term delivery characterized by low serum ß hCG level was met in a 32 year old lactating mother, who resumed normal menstruation after three months of cesarean section up to three cycles followed by amenorrhea for eight months; evacuation for presumed missed abortion prompted the diagnosis of PSTT which at the time of hysterectomy was found invading perimetrium and perforating the uterine cesarean scar. Conclusion: Careful evaluation of lactational amenorrhea is indicated so that the diagnosis of PSST may not be missed in the background of elusive picture such as missed abortion with low serum ß hCG, histological examination of the evacuated material may be relied which may provide the diagnosis at times. Key words: Placental site trophoblastic tumour (PSTT), hysterectomy, low serum ß hCG   doi:10.3126/njog.v3i1.1443 NJOG 2008 May-June; 3(1): 55 - 57